Mobility and movement rights in Malaysia: the constitutional ultimatum / Muhammad Izwan Ikhsan, Saslina Kamaruddin and Ku Mohd Amir Aizat Ku Yusof - Ikhsan, Muhammad Izwan; Kamaruddin, Saslina; Ku Yusof, Ku Mohd Amir Aizat (Universiti Teknologi MARA, Sabah, 2022)
The Constitution of Malaysia protects freedom of movement. However, national security, public order, public health, punishment of offenders, subversion, emergency and special immigration rules in Sabah and Sarawak restrict mobility rights under the Constitution. The purpose of this article is to examine the scope and characteristics of freedom of movement under the Malaysian Constitution, as well as the reasons for restricting such rights. The freedom of movement in Malaysia is limited because of the extensive exclusions that can be used to deny such rights. This article concludes that individual movement rights should be balanced against competing goals to maintain national security, public health, offender punishment, subversion, and emergency.